Fifth Five-Year Plan Tamil Nadu Draft Annual Plan 1976-77 Narrative Notes on Programmes - Planning Commission (Planning Commission, 1976)
It is proposed to conduct 125 job courses, 40 orientation courses and 30 refresher courses to the Officers of various categories of this Department. The financial provision is towards the Pay and Allowances of the staff and also for the Audio Visual Aids for the Institute. For intensifying research on Banana, a research station has been exclusively established in Virinchipuram near Vellore in North Arcot district. The provision made for 1975-76 is for the digging of two open wells and construction of two pump houses. For 1976-77, a provision of Rs. 039 lakh has been made towards the cost of land to be paid to the Devasthanam.
Narrative Notes on Programmes
Government of Tamil Nadu